Nanoscale Imaging of High‐Field Magnetic Hysteresis in Meteoritic Metal Using X‐Ray Holography. (3rd August 2020) - Blukis, R.; Pfau, B.; Günther, C. M.; Hessing, P.; Eisebitt, S.; Einsle, J.; Harrison, R. J.
Abstract: Stable paleomagnetic information in meteoritic metal is carried by the "cloudy zone": ~1–10 μm‐wide regions containing islands of ferromagnetic tetrataenite embedded in a paramagnetic antitaenite matrix. Due to their small size and high coercivity (theoretically up to ~2.2 T), the tetrataenite islands carry very stable magnetic remanence. However, these characteristics also make it difficult to image their magnetic state with the necessary spatial resolution and applied magnetic field. Here, we describe the first application of X‐ray holography to image the magnetic structure of the cloudy zone of the Tazewell IIICD meteorite with spatial resolution down to ~40 nm and in applied magnetic fields up to ±1.1 T, sufficient to extract high‐field hysteresis data from individual islands. Images were acquired as a function of magnetic field applied both parallel and perpendicular to the surface of a ~100 nm‐thick slice of the cloudy zone. Broad distributions of coercivity are observed, including values that likely exceed the maximum applied field. Horizontal offsets in the hysteresis loops indicate an interaction field distribution with half width of ~100 mT between the islands in their room temperature single‐domain state, providing a good match to first‐order reversal curve diagrams. The results suggest that future models of remanence acquisition in the cloudy zone should take account of strong interactions in order to extract quantitative estimates of the paleofield. Plain Language Summary: Magnetic fields played a significant role in the formation of the solar system and the evolution of the early planetary bodies in the first few million years after solar system formation. Knowledge about magnetic fields in the early solar system can be obtained from meteorites. Some meteorite types contain abundant iron‐nickel alloy that contains nanoscale "cloudy zone" regions (named after their appearance in an optical microscope) that can preserve magnetic information over 4.5 billion years. The cloudy zone is a complex material consisting of magnetically stable nanoscale particles embedded in a nonmagnetic matrix in very close proximity to one another. The fine scale and extreme magnetic stability of the cloudy zone make it challenging to study using conventional magnetic microscopy techniques. Here, we apply X‐ray holography for the first time to image the magnetization of individual magnetic particles and how they respond to magnetic fields. This new approach enables us to measure the magnetic properties of individual nanoscale particles, providing the first direct measurement of their magnetic stability and the strength of particle interactions. These measurements will improve our understanding of the magnetic information carried by the cloudy zone, and of how to extract information about solar system magnetic fields. Key Points: X‐ray holography enables magnetization of natural samples to be imaged with ~40 nm resolution and in applied magnetic fields up to ±1.1 T Meteoritic cloudy zone consists of strongly interacting single‐domain particles with single‐particle coercivities up to 1 T Average interaction fields between particles in the cloudy zone are of the order 100–200 mT